A long fatal love chase - Alcott, Louisa May, 1832-1888. (New York : Random House, 1995)
Yearning for romance and adventure, strong-willed eighteen -year-old Rosamond Vivian is seduced by the wealthy Phillip Tempest and is forced to flee his violent tendencies.
A novel.
Keywords: Married women -- Europe -- Fiction; Relationship addiction -- Fiction; Separation (Psychology) -- Fiction; Obsessive-compulsive disorder -- Fiction; Romantic suspense fiction; Love stories